Memory and the Patterns of Masculinity and Femininity in Contemporary Travel Writing: A Study of Madani wa Hawa’i by Lutfiya al-Dulaimi as a Model - محسن, هديل ياس عبد الحمزة (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study aims to address the Issue of the concept of memory (the memory of the journey) and the masculine cultural pattern it entails, as women’s writing is considered a carrier and expression of that social and cultural position that is condescending and arrogant in its view of female creativity, in accordance with the rule: If the hen crows like a rooster, slaughter it. However, the matter did not stop there, but rather extended to women’s participation in establishing that rule.